-13=ab-b-10

Simple and best practice solution for -13=ab-b-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13=ab-b-10 equation:


Simplifying
-13 = ab + -1b + -10

Reorder the terms:
-13 = -10 + ab + -1b

Solving
-13 = -10 + ab + -1b

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1ab' to each side of the equation.
-13 + -1ab = -10 + ab + -1ab + -1b

Combine like terms: ab + -1ab = 0
-13 + -1ab = -10 + 0 + -1b
-13 + -1ab = -10 + -1b

Add '13' to each side of the equation.
-13 + 13 + -1ab = -10 + 13 + -1b

Combine like terms: -13 + 13 = 0
0 + -1ab = -10 + 13 + -1b
-1ab = -10 + 13 + -1b

Combine like terms: -10 + 13 = 3
-1ab = 3 + -1b

Divide each side by '-1b'.
a = -3b-1 + 1

Simplifying
a = -3b-1 + 1

Reorder the terms:
a = 1 + -3b-1

See similar equations:

| 9(x+8)=4(2x+18)+x | | y^3+2y^2=2y+50 | | -11.2+4(2.1+q)=-.8 | | x-8.4=-5.2 | | N+5=21 | | 3[3(b-5)+17]-[3(3b-2)+5]= | | 2t+8=-5 | | 56.25=.50(x+4)(2) | | 5x-12=7x+4 | | X+9=-(2x+2) | | 33-6x=-24 | | 2x^3-72x= | | 3+4(3n+6)-n= | | p^2-6p+5=0 | | [9(b+4)-15]-[3(b-4)+3]= | | bc=3x+2 | | .05x+13=9 | | 5r-2r+3=7r-r | | 7x^2-7x-84= | | -2y=10x+16 | | (3x+5)(x+3)=7 | | 6x-y+5=180 | | 7x-248+x+44=180 | | 30-4x=14 | | 5(x-7)=2(2-2x)-3 | | [9(x+5)-16]+[3(x-2)+4]= | | x+8-1/3=90/11 | | 2x^2+8x-192=0 | | 3x+(x*x)=180 | | 0.06(10-x)(100)= | | x^2-5x=x(5+x) | | x^2-5x=x(5x) |

Equations solver categories